Philosophies of India - "Zimmer, Heinrich" (London, 1953)
A monumental work, Philosophies of India is divided into three main sections: The Highest Good, a discussion of Eastern and Western thought and their meeting and of the foundations of Indian Philosophy, The Philosophies of Time, Being the Philosophies of Success, Of Pleasure and of Duty, Finally The Philosophies of Eternity, This forms the Major Portion of the Work, Explaining Jainism, Sankhya and Yoga, Brahmanism, Buddhism and Tantra.
Keywords: "Philosophy, Indic."